1973
DOI: 10.1111/j.1751-1097.1973.tb06401.x
|View full text |Cite
|
Sign up to set email alerts
|

THE QUENCHING OF TYROSINE AND TRYPTOPHAN FLUORESCENCE BY H2O AND D2O*

Abstract: Abstract— The quantum yields and lifetimes of the fluorescence of tyrosine and tryptophan were determined in D2O‐H2O and glycerol‐H2O solvent mixtures of varying composition from 10 vol.% to 100% H2O at 15°C. Forboth amino acids the ratio of the quantum yields in D2O and H2O (i.e., qD/qH) was smaller than the ratio of the corresponding lifetimes (D/H). For tyrosine the ratio of the quantum yields in glycerol and H2O (qG/qH) was also smaller than the corresponding G/H ratio, but for tryptophan qG/gHG/H. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

1975
1975
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 21 publications
5
13
0
Order By: Relevance
“…In contrast to the fluorescence spectra, the H-D exchange of the indole-ring imino-proton leads to rather small changes of the UV-absorption spectra for tryptophan molecules (Nakanishi et al, 1978). Though several explanations of the solvent-isotope effect on the quantum yields can be found in the literature (Stryer, 1966;Eisinger & Navon, 1969;Kirby & Steiner, 1970;McGuire & Feldman, 1973), it is felt that a clear-cut mechanism is still missing.…”
Section: The Solvent-isotope Q{l~'et Of the Fluorescence Quantttm Yiementioning
confidence: 92%
See 1 more Smart Citation
“…In contrast to the fluorescence spectra, the H-D exchange of the indole-ring imino-proton leads to rather small changes of the UV-absorption spectra for tryptophan molecules (Nakanishi et al, 1978). Though several explanations of the solvent-isotope effect on the quantum yields can be found in the literature (Stryer, 1966;Eisinger & Navon, 1969;Kirby & Steiner, 1970;McGuire & Feldman, 1973), it is felt that a clear-cut mechanism is still missing.…”
Section: The Solvent-isotope Q{l~'et Of the Fluorescence Quantttm Yiementioning
confidence: 92%
“…spectroscopists that among other fluorescent molecules indole derivatives show a solventisotope effect of the fluorescence quantum yields with q~i~2o > ~Heo (Stryer, 1966;Eisinger & Navon, 1969;Kirby & Steiner, 1970;McGuire & Feldman, 1973;ttoss, 1975). Chemical modifications at the indole-ring nitrogen have revealed that neither H-or Dbonds (the crystalline structure of tryptaminc HCI shows only a weak hydrogen-bond of the indole NH to a chloride ion 3.2fl, away (Wakahara, Fajiwara & Tomita, 1973)) nor the H-D exchange of the indole N-proton are solely responsible for the solvent-isotope effect of the fluorescence quantum yield (Eisinger & Navon, 1969).…”
Section: The Solvent-isotope Q{l~'et Of the Fluorescence Quantttm Yiementioning
confidence: 95%
“…5 Fluorescence lifetimes were measured a t l5OC with a TRW nanosecond spectral source to a reproducibility of + 0.1 nsec, although the accuracy was probably -10%. A 270-nm interference filter (Optics Technology) was placed in the excitation path, and a 7-51 filter (Corning 5970) was used in the emission path.…”
Section: Fluorescence Lifetime Spectra and Intensity Measurementsmentioning
confidence: 99%
“…Additional evidence for this conclusion is the complete insensitivity of the fluorescence lifetime and quantum yirld (Figure l a ) of BSA to a fivefold increase in solvent viscosity, i.e., 1.1-5.5 cp, produced by addition of glycerol to an aqueous solution up to 50% v/v, M hereas this solvent change increased both the quantum yield and the lifetime of free tryptophan about 40'%. 5 This lack of dependence on viscosity does not necessarily eliminate Class I1 as the proper designation for any fluorescent tryptophan in aqueous BSAd since it can be argued that the mean molecular diameter of glycer~l,~' 3.2 A, prevents its penetration into small hydrophilic crevices in which Class I1 residues would be expected to reside. Howcver, over the 0-.50% glycerol range there is a blue shift of 6 nm in the A, , , (Figurc Ib) of the BSA fluorescence (260-290-nm c.xcitation) , which is twice as large as one observes for free tryptophan over the same solvent composition range.…”
Section: Effect Of Glycerolmentioning
confidence: 99%
“…Studies of tyrosine spectral/photophysical properties in organic solvents or their mixtures with water have got little attention in spite of the similarities in the protein matrix environment and organic solvent. Absorption spectra and ultraviolet circular dichroism of tyrosine and its derivatives in organic solvents and/or their mixtures with water were studied by Chignell and Gratzer (35), Horwitz et al (36), Bailey et al (37), Schlessinger et al (38), Stricland et al (39) and Smith (40), whereas their photophysical properties were studied by Guzow et al (15), Noronha et al (26), Feitelson (41), Froehlich and Yeats (42) and McGuire and Feldman (43). The quenching of tyrosine fluorescence in water‐organic solvent mixture is attributed to a tyrosine‐water exciplex, the formation of which is independent of bulk viscosity and the dielectric constant (42, 43).…”
Section: Introductionmentioning
confidence: 99%